A Novel Photosensitizer for Lipid Droplet–Location Photodynamic Therapy - Xia, Xiang; Wang, Ran; Hu, Yingqi; Liu, WeiJian; Liu, Ting; Sun, Wen; Fan, Jiangli; Peng, Xiaojun (Frontiers in Chemistry, 2021)
Lipid droplets (LDs), an extremely important cellular organelle, are responsible for the storage of neutral lipids in multiple biological processes, which could be a potential target site for photodynamic therapy (PDT) of cancer. Herein, a lipid droplet-targeted photosensitizer (BODSeI) is developed, allowing the fluorescence imaging-guided PDT. Owing to the location at lipid droplets, BODSeI demonstrates enhanced PDT efficiency with an extremely low IC50 value (around 0.125 nM). Besides, BODSeI shows good biocompatibility and high photostability. Therefore, BODSeI is promising for droplet-location PDT, which may trigger wide interest for exploring the pathway of lipid droplet-location PDT.